The kinetic fragility of Pt-P- and Ni-P-based bulk glass-forming liquids and its thermodynamic and structural signature. (15th June 2017) - Gross, Oliver; Bochtler, Benedikt; Stolpe, Moritz; Hechler, Simon; Hembree, William; Busch, Ralf; Gallino, Isabella
Abstract: The thermodynamic and kinetic properties of Pt-P- and Ni-P-based bulk glass-forming liquids are investigated using differential scanning calorimetry and three-point beam bending. The kinetic fragility of the alloys is determined by measuring relaxation times and equilibrium viscosities. In the Pt-P-based alloy family a Pt-rich alloy is one of the most fragile bulk glass-forming liquids in the vicinity of the glass transition reported so far. The fragility parameter D ∗ increases significantly with decreasing Pt-content, which is due to a more pronounced loss of excess entropy upon undercooling for the fragile liquids. Relying on previous observations made for Pd-P-based alloys, it is argued that a bifurcation of the P environment into Pt-Ni-P and Pt-Cu-P structural units stabilizes the deeply undercooled liquid due to formation of medium range order (MRO). This is supported by synchrotron X-ray scattering experiments, which reveal the formation of a pre-peak in the total structure factor with increasing fragility. Adapting a previously reported empirical correlation, we show that the more fragile liquid alloys are characterized by a more pronounced dilatation of atomic pair correlations on the length scale of 1 nm, corroborating the idea that the observed fragility behavior of Pt-P-based bulk glass-forming liquids is inherently related to structural changes on the length scale of MRO. Graphical abstract: Image